Team entitativity and teacher teams in schools: Towards a typology - Vangrieken, Katrien; Dochy, Filip; Raes, Elisabeth; Kyndt, Eva (Frontline Learning Research, 2013)
In this article we summarise research that discusses ‘teacher teams’. The central question guiding this study is ‘What types of teacher teams are there in schools and can they rightfully be called ‘teams’ or are they merely groups?’. We attempted to answer this question by searching literature on teacher teams and comparing what these articles present as being teacher teams. We attempt to further grasp the concept of teacher teams by creating a typology for defining different types of teacher teams. Overall, the literature pertaining to teacher teams appeared to be characterised by a considerable amount of haziness and teacher ‘teams’ mostly do not seem to be proper ‘teams’ when bearing the criteria of a team as defined by Cohen and Bailey (1997) in mind. The proposed typology, characterising the groups of teachers by their task, whether they are disciplinary or interdisciplinary, whether they are situated within or cross grades en by their temporal duration, seems to be a useful framework to further clarify different sorts of teacher ‘teams’.